FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT PENGGANGGURANDI PROVINSI SULAWESI UTARA - Arfan ., Poyoh; Gene H. M. Kapantow; Juliana R. Mandei (Sam Ratulangi University, 2017)
The study aims to analyze the factors - factors affecting the level of unemployment in theprovince of North Sulawesi. These factors include wages, inflation and GDP growth. This study usesmultiple linear regression analysis with Ordinary Least Square method (OLS) was performed using14 years data from 2001 to 2014. The results showed wage variables significantly influence theunemployment rate in North Sulawesi province with probability 0.0104, while inflation and levels ofGDP growth does not significantly influence the unemployment rate with respective probabilities0.5619 for Inflation and 0.3791 for GDP growth.Keywords: affecting factors, wages, inflation, GDP growth, unemployment, North Sulawesi Province